2016
DOI: 10.1103/physrevc.94.051303
|View full text |Cite
|
Sign up to set email alerts
|

TheMg30(t,p)Mg32“puzzle” reexamined

Abstract: We propose a phenomenological three-level mixing model of unperturbed 0p0h, 2p2h and 4p4h states, to describe the low-lying 0 + states in 32 Mg. Within this approach, self-consistent solutions exist that provides good agreement with the available experimental information obtained from the 30 Mg(t,p) 32 Mg reaction. The inclusion of the third state, namely the 4p4h configuration, resolves the "puzzle" that results from a two-level model interpretation of the same data. In our analysis, the 32 Mg ground state em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 13 publications
2
68
1
Order By: Relevance
“…Although this result was obtained in an empirical analysis by a one-parameter mixing of three 0 + states and the structure of 30 Mg taken in [61] differs from the present one, it is of interest that such large probabilities were obtained in both works independently.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Although this result was obtained in an empirical analysis by a one-parameter mixing of three 0 + states and the structure of 30 Mg taken in [61] differs from the present one, it is of interest that such large probabilities were obtained in both works independently.…”
mentioning
confidence: 86%
“…After the submission of this paper, Macchiavelli et al reported [61] that the ground state of 32 Mg is dominated by 2p2h and 4p4h configurations with nearly equal probabilities. Although this result was obtained in an empirical analysis by a one-parameter mixing of three 0 + states and the structure of 30 Mg taken in [61] differs from the present one, it is of interest that such large probabilities were obtained in both works independently.…”
mentioning
confidence: 99%
“…In our studies of neutron-rich Ne, Mg and Si isotopes, we have performed calculations in sd space. As it is well known that excitation to pf -shell is very important for nuclei which belong to "island of inversion" [8], thus, we have also performed calculations in sd-pf shell.…”
Section: Formalismmentioning
confidence: 99%
“…The island of inversion at N = 20 has been the subject of intense theoretical works (see [2] and references therein, [14][15][16]). The shell-model calculations with the effective nucleon-nucleon interaction obtained from the extended Kuo-Krenciglowa theory [16] took into account the tensor and three-nucleon forces (3NF).…”
Section: Calculation Resultsmentioning
confidence: 99%
“…The N = 20 isotones with Z ≤ 12 are near or in the so called island of inversion [12] where the admixture of intruder f p states is essential, and the ordering of the intruder and normal configurations is inverted. A lot of experimental and theoretical efforts were devoted to clarify the underlying physics of the island of inversion (see [2] and references therein, [7,[13][14][15][16]). The experimental observation of J π = 15 negative-parity states gave support to the collapse of the N = 20 gap and the inversion between the neutron 1f 7/2 and 1p 3/2 levels below Z = 12 [13].…”
Section: Introductionmentioning
confidence: 99%